Integration of Smart Machine Presence Using RFID E-Money Cards for Employee Attendance Management at Universitas Negeri Semarang - Yanuarto, Alfath; Septian, Dinar Diaz; Munawar, Akhmad; Putra, Anggyi Trisnawan; Ramadhan, Andika Enggal; Kumorowati, Bhekti (International Journal of Active Learning, 2024)
The study aims to improve the effectiveness of the online attendance system at Universitas Negeri Semarang (UNNES). The existing system, reliant on web-based input via tokens and employee identification numbers, suffers from inefficiencies and potential inaccuracies due to proxy attendance. These limitations hinder productivity and the accuracy of performance appraisals. To address these challenges, a Smart Machine Presence system was designed and implemented, utilize RFID e-money cards which become employee Identification cards (ID Card)  to streamline the process and eliminate the need for manual input. This novel system employs Raspberry Pi 4 Model B technology, integrated with RFID readers and camera modules for robust authentication. The research utilized a three-stage approach: system needs analysis, prototype design, and system development. Usability testing conducted with 20 participants using the System Usability Scale (SUS) yielded a score of 86.8, indicating high user satisfaction and effectiveness. The proposed system demonstrated significant advantages, including improved data validity, enhanced operational efficiency, and reduced resource costs compared to traditional systems. This study concludes that the Smart Machine Presence system is a cost-effective, efficient, and scalable solution for modern attendance management systems.